Vitamina D em mulhers adultas fumantes e ex-fumantes: ingestão, concentração sérica e associação com variáveis ecocardiográficas - Fidélix, Melaine Priscila [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Smoking is a risk factor for cardiovascular diseases. Experimental and clinical studies showed that the smoke inhalation of cigarette smoke leads to functional and morphological changes in the heart and this is negatively associated with serum vitamin D concentrations. In addition, there are reports of the association between vitamin D and cardiac remodeling. Thus, the objective was to determine whether the serum concentration of vitamin D and smoking habits explain the structural and functional cardiac variables in women and ex-smokers women compared to healthy women. Methods: Cross-sectional observational study in which 55 women were evaluated, 19 never smokers (control, 44,4±11 years), 18 active smokers (52,8±7 years) and 18 ex-smokers (51,7±8 years). It was evaluated the blood pressure, sun exposure questionnaire, dietary intake (24-hour recall in triplicate), body composition (weight, height, body mass index (BMI), circumferences (arm, waist, abdominal) and hip, bone mineral density, fat mass and fat-free mass X-ray absorptiometry dual energy absorptiometry (DXA)), laboratory analysis (serum calcium, total cholesterol and fractions, triglycerides, creatinine, urea, glucose, glycated hemoglobin, C-reactive protein, total proteins and fractions, parathyroid hormone (PTH), vitamina D (25(OH)D) and blood test), echocardiogram and spirometry. The results were analyzed using descriptive statistical tests, group comparisons, proportions, correlations and multiple linear regression, with significance level of 5%. Results: In three groups, BMI classification was overweight and values of waist circumference and waist/hip higher than the cutoffs for healthy women in all groups were observed. There was no difference between body composition variables. The concentrations of total and LDL cholesterol were higher in the group ex-smoker. Dietary intake of vitamin D and calcium was lower than those recommende by the EAR ...

O tabagismo é fator de risco para doenças cardiovasculares. Estudos experimentais e clínicos mostraram que a inalação da fumaça do cigarro leva a alterações funcionais e morfológicas no coração e está associado negativamente com as concentrações de vitamina D séricas. Além disso, há relatos da associação da vitamina D e remodelação cardíaca. Sendo assim, o objetivo foi verificar se a concentração sérica de vitamina D e hábito tabágico explicam as variáveis funcionais e estruturais cardíacas em mulheres fumantes e ex-fumantes comparados a mulheres saudáveis. Metodologia: Estudo observacional transversal, no qual foram avaliadas 55 mulheres, sendo 19 que nunca fumaram (controle, 44,4±11 anos), 18 fumantes ativas (52,8±7 anos) e 18 ex-fumantes (51,7±8 anos). Foram avaliadas pressão arterial, questionário de exposição solar, ingestão alimentar (recordatório de 24 horas em triplicata), composição corporal (peso, altura, índice de massa corporal (IMC), circunferências (braço, cintura, abdominal e quadril), densidade mineral óssea, massa gorda e massa magra por absortometria por raios X de dupla energia (DEXA)), análise laboratorial (concentrações séricas de cálcio, colesterol total e frações, triglicérides, creatinina, ureia, glicose, hemoglobina glicada, proteína C-reativa, proteínas totais e frações, paratormônio (PTH), vitamina D (25(OH)D) e hemograma), ecocardiograma e espirometria. Os resultados foram analisados por meio de testes estatísticos descritivos, comparações de grupo, proporções, correlações e regressão linear múltipla, com significância de 5%. Resultados: Nos três grupos, a classificação do IMC foi sobrepeso e foram observados valores de circunferência abdominal e relação cintura/quadril maiores do que os pontos de corte para mulheres saudáveis em todos os grupos. Não houve diferença entre as variáveis de composição corporal. As concentrações de colesterol ...
Keywords: Vitamina D; Mulheres - Doenças; Mulheres - Fumantes; Coração - Doenças; Ecocardiografia; Heart Diseases